ANALYSIS OF DESIGN AND IMPLEMENTATION OF INFORMATION SYSTEM OF LIBRARY OF UIN SUNAN KALIJAGA JOGYAKARTA - Hendra Junawan (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2020)
The purpose of writing this article is to find out how to design and implement the Information System of the Sunan Kalijaga State Islamic University Yogyakarta Library which is supported by the System Development Life Cycle (SDLC). The method used in this study is the type of field research that is "field research" which has the nature of skin research and data collection techniques with direct observation and information obtained through documentation in the field. The results and discussion in this article show that CYPRUS (Library Information System) has the task of collecting, processing, preserving, reinventing information, borrowing and returning books in the circulation section, already using information technology to store data and library collections, in the design process This library information system also uses the MySQL database in streamlining the library information system, and from the plan, it can be used by the admin and librarian and the results are shown in the library information system design show that there is data collection on the members, login columns, member data types, display reports free library, and display collection returns and borrowing columns.Design and Implementation, Library Information System.